Implementation of Gemu Fa Mi Re Exercise in Reducing Blood Pressure in Hypertension Patients - Padamani, Mia Ina; Making, Maria Agustina; Sambriong, Maria; Namuwali, Domianus; Kapitan, Meiyeriance (GLOBAL HEALTH SCIENCE GROUP, 2023)
Hypertension is a chronic disease which is called a silent killer because it often does not cause complaints, so sufferers do not know they have hypertension and only find out after complications occur. (Maria et al., 2021). The aim of this research is to determine the application of gemu fa mi re exercise in lowering blood pressure in hypertensive patients in the working area of the Sikumana Community Health Center, Kupang City. The research design was descriptive, the total research sample was 30 respondents using purposive sampling technique. Data collection was carried out by interviews and fa mi re exercise interventions for hypertensive patients in the Sikumana Community Health Center working area. The procedure was carried out for 3 days with a time of 20 minutes, measuring pre-test and post-test blood pressure. Analyzing the data using univariate research results, it was found that the majority of gender characteristics were women, 23 people, the majority of respondents were >45 years old. High school education 23 people. The majority of respondents did not work or were retired, namely 23 people. The duration of hypertension for 1 year was 18 people. There were 6 people in the pre-hypertension blood pressure category and 24 people in stage 1 hypertension. Gemu fa mi exercise can lower blood pressure, with a decrease in systole and diastole of 5 to 20 mmHg with an average decrease in systole of 5 mmHg and diastolic of 10 mmHg. Conclusion: Gemu fa mi re exercise can reduce blood pressure in hypertension sufferers. Suggestion: Health workers who work in the Sikumana Community Health Center area can improve the non-communicable disease (NCD) program with culturally based efforts to reduce blood pressure such as doing gemu fa mi re exercises.